Face-to-Face vs. E-Learning Models in the COVID-19 Era: Survey Research in a Spanish University - María Teresa Costado Dios; José Carlos Piñero Charlo (MDPI AG, 2021)
This study shows the results of an autobiographical questionnaire of Spanish university students regarding two different educational models caused by the COVID-19 pandemic: face-to-face and e-learning. The aim is to discover their perceptions and opinions about their experiences during the learning process and what they have experienced during this global emergency and period of home confinement. The sample is made up of 100 students from the Primary Education Degree programme and the research was carried out through a qualitative study of the questionnaire. The results, divided into categories of each educational model, show the interpretation that the students make of the current reality and their own learning process. The most important aspect of the face-to-face learning model, according to 75% of the students, is direct communication with the teacher, and for 88% of them this model was effective. For the e-learning model, the flexible schedule, the economic savings and explanatory videos are the relevant ideas that the students express, with 68% stating that it was an effective model. The main conclusion is that the students prefer to continue with the face-to-face learning process (49%) rather than online teaching (7%) or, failing that, mixed or blended learning (44%), where the theoretical classes could be online and the practical classes could be face-to-face.